1976
DOI: 10.1063/1.322475
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the secondary electron emission coefficient of argon on Paschen breakdown curves in ac plasma panels for neon+0.1% argon mixture

Abstract: A generalized expression has been derived for the effective secondary electron emission coefficient γ, in Penning mixtures which incorporates the effect of both the majority and minority ions. Specific calculations for ac panels having an Ne+0.1%Ar mixture show that even a relatively small value of γAr not only significantly lowers the breakdown voltages, but also moves the voltage minimum to higher p0d values and makes the right-hand side of the Paschen curve less steep. This sensitivity of the effective coef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

1978
1978
2009
2009

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 5 publications
(1 reference statement)
0
11
0
Order By: Relevance
“…Sahni and Lanza developed a one-dimensional ͑1D͒ fluid model 6 and demonstrated that the secondary electron emission from the dielectrics has a strong influence on the dynamics of a neon-based monochrome PDP. 7,8 Veerasingam, Campbell, and McGrath developed both 1D and 2D fluid models for PDPs [9][10][11] which were applied to the operation of He and He/Xe based opposingelectrode PDP cells. Their computed results qualitatively agreed with experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Sahni and Lanza developed a one-dimensional ͑1D͒ fluid model 6 and demonstrated that the secondary electron emission from the dielectrics has a strong influence on the dynamics of a neon-based monochrome PDP. 7,8 Veerasingam, Campbell, and McGrath developed both 1D and 2D fluid models for PDPs [9][10][11] which were applied to the operation of He and He/Xe based opposingelectrode PDP cells. Their computed results qualitatively agreed with experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Computer simulations may be invaluable to understand the basic properties of plasma and the mechanism of VUV emission. [8][9][10][11][12][13][14][15][16][17][18][19][20] In this article, in order to optimize composition and pressure of the Ne-Xe mixture gas to get higher discharge efficiency, a global model of a dielectric barrier discharge in Ne-Xe mixtures for the AC-PDP was developed. The model was used to evaluate electron temperature, plasma density, densities of excited state atoms, wall charge density, current density, excimer density, and VUV intensity, and their gas composition-pressure dependencies.…”
Section: Introductionmentioning
confidence: 99%
“…He also found y, = 0.52 for MgO films fired in dry air at 500°C [9]. Ahearn and Sahni [7] have argued that excess oxygen produced a large density of acceptor states near the top of the valence band from which Auger electrons of increased energy were emitted, while Sahni and Lanza [10] have theoretically explained that the excess energy of these electrons modified the dependence of y. on the reduced electric field at the cathode [11,12] and thereby increased V^ and the margin. Although the use of MgO has been reported elsewhere [6,13,14], comparison of the voltage levels was not possible because the linewidth, chamber spacing, gas composition, and pressure, as well as the processing conditions, were not the same.…”
Section: Initial Operationmentioning
confidence: 99%